The effect of SP6 acupressure technique on reducing dysmenorrhea and anxiety in adolescent girls - Hana Haryani (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Adolescent girls experience biological changes in the form of menstruation, which is often accompanied by dysmenorrhea and anxiety. One non-pharmacological approach to reducing dysmenorrhea and anxiety in adolescent girls is acupressure on the SP 6 point. Objective: This study aimed to determine the effect of acupressure on the SP 6 point on reducing dysmenorrhea and anxiety in adolescent girls. Methods: This quasi-experimental study employed a pretest–posttest control group design involving 30 adolescents, with 15 participants in each group selected through purposive sampling. Acupressure was administered three times for 30–60 seconds at 1-hour intervals. Dysmenorrhea and anxiety were assessed using the Numeric Rating Scale (NRS) and General Anxiety Disorder-7 (GAD-7) instruments, respectively. Data were analyzed using paired sample and independent sample t-tests. Results: The results showed a decrease in dysmenorrhea from 5.20 to 2.33 and a decrease in anxiety from 10.33 to 2.33 after the SP 6 acupressure technique was administered. There was an effect of acupressure on SP 6 points on the reduction of dysmenorrhea and anxiety in adolescent girls, and there is a difference in dysmenorrhea and anxiety with a p-value <0.001 (<0.05). Conclusion: The findings of this study indicate that acupressure on the SP6 point has the potential to be an effective non-pharmacological intervention in reducing dysmenorrhea and anxiety in adolescent girls and can serve as a basis for further research on adolescent reproductive health management.